Metabolite Profiles and Biological Activities of Different Phenotypes of Beech Mushrooms (Hypsizygus marmoreus) - Sang-Wook Jeong; Hyeon Ji Yeo; Neul-I Ha; Kyung-Je Kim; Kyoung-Sun Seo; Seong Woo Jin; Young-Woo Koh; Hee Gyeong Jeong; Chang Ha Park; Seung-Bin Im (Foods)
Beech mushrooms (Hypsizygus marmoreus) are edible mushrooms commercially used in South Korea. They can be classified into white and brown according to their pigmentation. This study analyzed the metabolites and biological activities of these mushrooms. Specifically, 42 metabolites (37 volatiles, two phenolics, and three carbohydrates) were quantified in white beech mushrooms, and 47 (42 volatiles, two phenolics, and three carbohydrates) were detected in brown mushrooms. The major volatiles detected were hexanal, pentanal, 1-hexanol, and 1-pentanol. Brown mushrooms contained higher levels of hexanal (64%) than white mushrooms (35%), whereas white mushrooms had higher levels of pentanal (11%) and 1-pentanol (3%). Most volatiles were more abundant in white mushrooms than in brown mushrooms. Furthermore, brown beech mushrooms had a higher phenolic content than white mushrooms. Biological assays revealed that both types of mushroom demonstrated anti-microbial activities against bacterial and yeast pathogens and weak DPPH scavenging activity. The extracts from both mushrooms (50 μg/mL) also exhibited strong anti-inflammatory properties. Brown mushroom extracts showed higher antioxidant, anti-microbial, and anti-inflammatory properties than white mushroom extracts. This study reported that the differences in phenotype, taste, and odor were consistent with the metabolite differences between white and brown beech mushrooms, which have high nutritional and biofunctional values.